2020
DOI: 10.1016/j.biortech.2020.123412
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis and fermentation steps of a pretreated sawmill mixed feedstock for bioethanol production in a wood biorefinery

Abstract: The aim was to demonstrate the feasibility of second-generation bioethanol production using for the very first time a sawmill mixed feedstock comprising four softwood species, representative of biomass resource in Auvergne-Rhône-Alpes region (France). The feedstock was subjected to a microwave-assisted water/ethanol Organosolv pretreatment. The investigation focused on the enzymatic hydrolysis of this pretreated sawmill feedstock (PSF) using Cellic ® Ctec2 as the enzyme, followed by fermentation of the resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The concentrations of reducing sugars released using the higher amount of enzyme (30 U/g of Celluclast or 30 FBGU/g of Viscozyme) at 24 h were approximatively the same after 48 h of enzymatic treatment. The hydrolysis efficiency was significantly increased at the beginning of the reaction and became stable after 24 h. The same conclusions were reported by Abdou Alio, et al (2020) [37] after enzymatic hydrolysis on a wet pretreated sawdust mixture with both 50 and 70 FPU/g enzyme. Moreover, in another study reported by Guerrero, et al [38], the bioethanol production from banana waste was studied at different enzyme concentrations (7.5-22.5 FPU/g −1 of glucan) using Celluclast 1.5 L and Novozym 188.…”
Section: Effect Of Enzyme Loadingsupporting
confidence: 88%
“…The concentrations of reducing sugars released using the higher amount of enzyme (30 U/g of Celluclast or 30 FBGU/g of Viscozyme) at 24 h were approximatively the same after 48 h of enzymatic treatment. The hydrolysis efficiency was significantly increased at the beginning of the reaction and became stable after 24 h. The same conclusions were reported by Abdou Alio, et al (2020) [37] after enzymatic hydrolysis on a wet pretreated sawdust mixture with both 50 and 70 FPU/g enzyme. Moreover, in another study reported by Guerrero, et al [38], the bioethanol production from banana waste was studied at different enzyme concentrations (7.5-22.5 FPU/g −1 of glucan) using Celluclast 1.5 L and Novozym 188.…”
Section: Effect Of Enzyme Loadingsupporting
confidence: 88%
“…This process has potential to explore further, provided safety and cost of the process is regulated [60]. A microwave-assisted ethanol-organosolv pretreatment showed enzymatic hydrolysis of cellulose up to 80% at 1.5% substrate consistency; however, scale up of the enzymatic hydrolysis step using higher substrate concentrations of 7.5% decreased enzymatic hydrolysis of cellulose to almost 60% [61]. Recently, ultrasonic and microwave (480 W)-assisted ethylene glycol (94 wt%) organosolv pretreatment performed at 150 °C on pine wood produced levoglucosan (55.9 wt%), hemicellulosic sugars (20 wt%) and phenols (14 wt%).…”
Section: Other Organosolv Pretreatmentsmentioning
confidence: 99%
“…2, the percent enzymatic hydrolysis of softwood cellulose data is plotted against severity factor (S 0 ) and pretreatment temperature as applied in different ethanol organosolv pretreatments in the literature. The pH of organosolv [52,61] process in the presence of catalyst is not often reported in the literature and those reported are the starting pH, which gradually changes over the course of the organosolv reaction. Therefore, S 0 values in Fig.…”
Section: Effect Of Pretreatment Severity and Temperaturementioning
confidence: 99%
“…In some processes a purer distillate is required, which is in contrast to the amount that can be obtained. In general, the longer the column and the larger the contact surface within the column, the more effective the separation of the components will be, although it also depends on other factors (Abdou et al, 2020).…”
Section: Composition Profiles and Molar Flowsmentioning
confidence: 99%
“…However, stand-alone bioprocesses can present high operational costs, which can be reduced by process integration with a consolidated facility (Olofsson et al, 2017;Zhou et al, 2018;Sharma et al, 2020). In order to meet these supply needs while providing an economically viable option, the concept of biorefinery production was created (Abdou et al, 2020;Battista et al, 2019;Gil et al, 2014;Li et al, 2016;Morales et al, 2017;Morales et al, 2021).…”
Section: Introductionmentioning
confidence: 99%